Carga inmediata sobre implantes: una posibilidad protésica - Arismendi-Echavarría, Jorge Alberto; Agudelo-Arismendi, Lina Patricia; López, Fernan Diego (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Dr. Branemark introduced the term osseointegration as anew concept in endosseous implant therapy. Long-term follow-up studies demonstrated a high success rateoSurgical and prosthetic protocol established certain conditions to get osseointegration, permiting a long healing time, 3-6 months, without functionalload. This original protocol has been changing over time. Tbis review shows how the immediate load can be aprosthetic possibility in the osseoin tegration techniq ue withou t being a risk factor.